IMPLEMENTASI TEKNOLOGI PENDIDIKAN SEBAGAI PROSES PERUBAHAN SISTEMIK: PERSPEKTIF DIFUSI INOVASI - Ghefira Naziha Zahara; Ahsanti Najiya; Astriana Jihan Kusumawati (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
Digital transformation in education has accelerated the adoption of learning technologies across educational institutions. However, technology implementation does not always run optimally, as it is influenced by multiple interrelated components within educational systems. This study aims to analyze educational technology implementation through a systems thinking approach and the innovation diffusion perspective. The study employed a Systematic Literature Review (SLR) method using a simplified Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) approach. Literature was collected from Scopus, ERIC, ScienceDirect, Web of Science, and Google Scholar databases covering publications from 2017 to 2025. The initial search identified 97 articles, followed by screening based on topic relevance, publication quality, and research focus, resulting in 42 eligible articles for further analysis, with 26 core articles included in the final synthesis. The findings indicate that educational technology implementation is a systemic process shaped by interactions among individual, organizational, technological, policy, and environmental factors. The innovation diffusion perspective explains how technology is adopted within educational social systems, while systems thinking helps explain dynamic relationships among educational components as a whole. The integration of these two perspectives produces a more comprehensive conceptual framework for understanding both the success and barriers of educational technology implementation. ABSTRAK Transformasi digital dalam pendidikan mendorong peningkatan penggunaan teknologi pembelajaran di berbagai lembaga pendidikan. Namun, implementasi teknologi tidak selalu berjalan optimal karena dipengaruhi oleh berbagai komponen dalam sistem pendidikan yang saling berinteraksi. Penelitian ini bertujuan menganalisis implementasi teknologi pendidikan melalui pendekatan berpikir sistemik dan perspektif difusi inovasi. Penelitian menggunakan metode Systematic Literature Review (SLR) dengan pendekatan Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) sederhana. Penelusuran literatur dilakukan melalui database Scopus, ERIC, ScienceDirect, Web of Science, dan Google Scholar pada artikel terbit tahun 2017–2025. Tahap awal memperoleh 97 artikel, kemudian setelah proses seleksi berdasarkan relevansi topik, kualitas publikasi, dan kesesuaian fokus penelitian, diperoleh 42 artikel untuk analisis lanjutan, dengan 26 artikel utama digunakan dalam sintesis inti. Hasil penelitian menunjukkan bahwa implementasi teknologi pendidikan merupakan proses sistemik yang dipengaruhi oleh interaksi faktor individu, organisasi, teknologi, kebijakan, dan lingkungan pendidikan. Perspektif difusi inovasi menjelaskan proses adopsi teknologi dalam sistem sosial pendidikan, sedangkan pendekatan berpikir sistemik membantu memahami keterkaitan dinamis antar komponen pendidikan secara menyeluruh. Integrasi kedua perspektif tersebut menghasilkan kerangka konseptual yang lebih komprehensif untuk menjelaskan keberhasilan maupun hambatan implementasi teknologi pendidikan.